Somatic and germline clone analysis in mutants of the S-adenosylmethionine synthetase encoding gene in Drosophila melanogaster. - Larsson, J.; Rasmuson-Lestander, A. (FEBS Letters, 1998)
We have analysed the phenotypic consequences of homozygous mutant clones in the S-adenosylmethionine synthetase encoding gene in Drosophila melanogaster. The results suggest that SamS function is required for cell proliferation/growth in embryonic/early larval cells and during development of imaginal disc cells. Homozygous SamS germline clones can, however, develop and give rise to viable heterozygous offspring. This offspring expresses a Minute-like phenotype. We suggest that this phenotype is caused by an obstruction of the polyamine biosynthesis.